The association between malaria incidences and air temperature at Kulon Progo District, Yogyakarta Special Province - . Nilasari; Lutfan Lazuardi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Malaria is still a public health problem in Indonesia including in Kulon Progo District, Yogyakarta Special Province. Kulon Progo District remains become malaria endemic area, with significant number of malaria cases for more than the last ten years. Previous studies proved that malaria transmission is associated with climatic conditions. However, these conditions have never been investigated in Kulon Progo District. The aim of this ecological study was to investigate the association between the distribution of malaria cases and climatic condition in the Kulon Progo District using spatial-temporal approach. A total of 1439 malaria cases were collected during the period of 2005-2015. Time-trend, bivariate analysis, and spatial analysis were performed. The results showed that air temperature lag 0 (p = 0.0000; r = 0.5225), air temperature lag 1 (p = 0.0009; r = 0.2850), air temperature lag 2 (p = 0.0329; r = 0.1858) related to the incidence of malaria. Spatial analysis and time-trend analysis also showed direct relationship pattern between malaria and air temperature. In conclusion, there is a relationship between malaria cases and air temperature in Kulon Progo District. Spatial analysis approach is important for early alert system, to decrease morbidity and mortality due to malaria.